2021
DOI: 10.1021/acs.jpclett.1c01254
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Thioflavin T Binding Modes to DNA: A Structure-Specific Molecular Probe for Lasing Applications

Abstract: The binding mechanism of thioflavin T (ThT) to DNA was studied using polarized light spectroscopy and fluorescence-based techniques in solutions and in solid films. Linear dichroism measurements showed that ThT binds to DNA duplex by intercalation. Time-resolved fluorescence studies revealed a second binding mode which is the external binding to the DNA phosphate groups. Both binding modes represent the nonspecific type of interactions. The studies were complemented with the analysis of short oligonucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…We also observed that the fluorescence behaviors of ThT upon binding to 32R-3n at 490 nm in K + and Li + were strongly dependent on the [ThT]/[32R-3n] ratio, as depicted in Figure 4C . At 8 μM 32R-3n, the fluorescence increased to a vertex in either K + or Li + , with the [ThT]/[32R-3n] ratio increasing up to ∼3–3.5 and, beyond this ratio, the fluorescence experienced a decrease, most probably due to the quenching effect of the post-bound ThT with the pre-formed psDNA by other binding modes at high ThT concentration on the pre-inserted ThT responsible for the psDNA formation ( 78 ). This vertex ratio means that 6–7 ThT molecules may be needed to switch G4 to the psDNA structure, suggestive of the role of molecule clustering in G4 switching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the fluorescence behaviors of ThT upon binding to 32R-3n at 490 nm in K + and Li + were strongly dependent on the [ThT]/[32R-3n] ratio, as depicted in Figure 4C . At 8 μM 32R-3n, the fluorescence increased to a vertex in either K + or Li + , with the [ThT]/[32R-3n] ratio increasing up to ∼3–3.5 and, beyond this ratio, the fluorescence experienced a decrease, most probably due to the quenching effect of the post-bound ThT with the pre-formed psDNA by other binding modes at high ThT concentration on the pre-inserted ThT responsible for the psDNA formation ( 78 ). This vertex ratio means that 6–7 ThT molecules may be needed to switch G4 to the psDNA structure, suggestive of the role of molecule clustering in G4 switching.…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, following the leading work of Li's group ( 2 ), several researchers have confirmed the ThT-induced psDNA formation for single-stranded GA-rich sequences ( 76 , 77 ). These DNA interactions subsequently turn on the MR fluorescence, dependent on the binding modes, DNA structures and sequences ( 78 ). However, the G4 switching by the MR clustering rationale has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, ThT , similar to TO dye, is a non-specific fluorescent probe that could interplay in various DNA structures in three different binding modes including intercalation, external binding and binding inside DNA cavities. 159 Therefore, the intracellular binding target of CQ in mitochondria may be not conclusive.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 99%
“…Недостатком данного красителя в контексте визуализации G-квадруплексов и i-мотивов является его низкая селективность, обусловленная способностью связываться также с другими структурами нуклеиновых кислот, включая двухцепочечную ДНК, трехцепочечную ДНК и РНК [27,29,30]. Обнаружено, что еще один флуоресцентный краситель, тиофлавин Т (ThT), широко применяющийся для специфического окрашивания амилоидов, также связывается с различными структурами ДНК, при этом усиление флуоресценции при связывании с G-квадруплексами особенно велико (в ~2100 раз в видимой области) [31,32]. За последние годы разработан и изучен ряд новых соединений для использования в качестве флуоресцентных зондов на G-квадруплексы и i-мотивы [33], в частности, производные бензотиазола [34,35].…”
Section: флуоресцентная микроскопия неканонических структур днкunclassified
“…The disadvantage of this dye in the context of the visualization of G-quadruplexes and i-motifs is its low selectivity, as it is able to bind to other nucleic acid structures as well, including double-stranded DNA, three-stranded DNA, and RNA [ 27 , 29 , 30 ]. Another fluorescent dye, thioflavin T (ThT), widely used for specific staining of amyloids, also binds to various DNA structures, while the fluorescence amplification upon binding to G-quadruplexes is especially high (~ 2,100-fold in the visible region) [ 31 , 32 ]. In recent years, a number of new compounds have been developed and studied in order to be used as fluorescent probes for G-quadruplexes and i-motifs [ 33 ], and benzothiazole derivatives in particular [ 34 , 35 ].…”
Section: Fluorescence Microscopy Of Non-canonical Dna Structuresmentioning
confidence: 99%